Grammar Error Patterns in The English Translation of The Maluku Folktale Batu Penyu.: - - Saumi, Rahma Ibtida; Ananda, Rahmania; Jannah, Miftahul; Syahid, Abdul (Universitas Negeri Medan, 2025)
In this article, the author examines the grammatical errors from the perspective of semantics, wrong meaning substitution, phrases, idioms, and other parts of the English translation of the Moluccan (Maluku) folktale Batu Penyu in terms of pedagogical translation structure and cultural heritage preservation. This study describes the systematic errors found in the translation from Indonesian and local languages of folktales into English that can reduce clarity and diminish comprehension value in the context of translation as an educational text for young learners. The study is set up as a descriptive qualitative analysis with AI, helps by ChatGPT-4Turbo and Gemini Advanced, spotting mistakes in a language system changed by Hawkins and Norton (2020) using a comparing method marked by G1 through G10 in the form of neat tables. There were 20 grammar mistakes; 5 syntax errors were the most major type followed by 4 lexical difficulty issues and 3 semantic mismatch cases. Findings from this study further illuminate the presence of cross-cultural language adaptation issues concerning idiomatic expressions and references. This study greatly contributes to the ongoing academic conversation regarding how appropriate translation can foster English as a Second Language acquisition and intercultural communication.